Fifteen years of follow-up of a removable prosthetic design to maintain two remaining molars in a patient with mandibular reconstruction - Ming-Lun Hsu; Jacqueline Chia-Hsuan Wu; Ling-Ming Yu (Elsevier, 2012)
This clinical report describes a long-term prosthetic solution for a patient who had undergone mandibular reconstruction with a fibular graft, leaving only two right molars. The only retention device for the removable prosthesis design included a telescoping system with an O-ring application, but without fibula graft involvement. This prosthesis design was motivated by the altered bony and muscular architecture resulting in an increased maxillomandibular space and thick soft tissue in the denture-bearing area. This case demonstrates that appropriate denture design, consistent recall maintenance, and oral hygiene motivation minimized periodontal destruction and maximized prosthetic use for the patient despite the unfavorable loading conditions.